A survey of the handweaving industry in some selected areas in Metro-Manila - Arribas, Lydia B.
The purpose of this study was to gather information on some aspects of the handweaving industry in certain areas in Metro Manila. data were gathered through questionnaires, interviews, and observation of twelve establishments in 1972 and 1976. Results revealed that handweaving was a cottage, small-scale industry with single proprietorship. Fifty percent of the establishments were started between 1969 and 1970. Among the owners, interest in handweaving was not determined by age and gender, but by their familiarity with the craft and its potentials as a profitable undertaking. There were more women than men weavers. Male weavers were assigned ion the production of Roman shades whereas the women weavers concentrated on soft fine fabrics. Mode and rate of payment for weavers varies. In addition to their basic pay, weavers also enjoyed free board and lodging or food allowance. Three-fourths of the weavers were live-ins. Raw materials consisted of cotton, ramie, and acrylic yarns of varying sizes as well as veneer slats and rattan wickers purchased from local suppliers. Products consisted of different items for clothing and home furnishing end-uses. In general, most of the establishments had adequate working areas, lighting, and ventilation. Storage facilities were from very inadequate to adequate. In as much as handweaving is an economic asset, it should receive substantial attention and support from both the government and private sectors in the country. It should be an integral part of the total man-power training program and of the management courses for cottage or small-scale industry. Maximizing the potentials of the industry may also call for organization of handweaving industry owners.